2015
DOI: 10.3892/ijmm.2015.2218
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of calcium ions on the apoptosis and onset of mineralization of human dental pulp cells in vitro and in vivo

Abstract: Calcium ions (Ca2+) are a major constituent of most pulp-capping materials and have an important role in the mineralization of human dental pulp cells (hDPCs). A previous study by our group has shown that increased levels of Ca2+ can promote hDPC-mediated mineralization in long-term cultures (21 days). However, the initiation of mineralization occurs in the early stage of osteogenic inductive culture, and the effects of Ca2+ on the mineralization of hDPCs in short-term cultures (five days) have not been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Increased viability after 72 h of immersion in MTA-Angelus and Odontocem was in accordance with a study by Peng et al, who reported significant proliferation in human pulp cells exposed to Ca 3 SiO 5 extract solution compared with growth medium from day 3 [15]. Calcium and silicate were also the main components of the materials used in this study [15,16].…”
Section: Discussionsupporting
confidence: 92%
“…Increased viability after 72 h of immersion in MTA-Angelus and Odontocem was in accordance with a study by Peng et al, who reported significant proliferation in human pulp cells exposed to Ca 3 SiO 5 extract solution compared with growth medium from day 3 [15]. Calcium and silicate were also the main components of the materials used in this study [15,16].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that an increase in calcium and phosphorus ions within a certain concentration range significantly promotes the osteogenic differentiation of mesenchymal stem cells. However, when the concentration of calcium and phosphorus ions is too high, apoptosis and necrosis will be triggered in cells, which are not beneficial for osteogenesis (An et al, ; Viti et al, ). Researchers have found that incubation of hDPSCs with 9.0 mM Ca 2+ for 24 hr may significantly increase the early rates of apoptosis and necrosis (An et al, ), while high phosphate concentrations (>2.5 mM) induced apoptosis in two endothelial cell lines (Di Marco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that extracellular fluid at sites of injury, infection, or inflammation contains high concentrations of calcium [ 43 ]. Interestingly, rapid resorption of CaSO 4 results in a Ca 2+ -rich fluid that could modulate inflammation and apoptosis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%